Strategi Pembelajaran Pendidikan Agama Islam dalam Menghadapi Tantangan di Era Revolusi Industri 5.0 - Musyafak, Musyafak; Subhi, Muhamad Rifa'i (Asian Journal of Islamic Studies and Da'wah, 2023)
This study explores the strategies and implementation of Islamic Religious Education at MTs Agung Alim Blado, facing the era of the 5.0 Industrial Revolution. The main focus is on the integration of Islamic values with technological advancements through interactive and innovative teaching methods. Qualitative methods are used to understand students' experiences and adopt a holistic approach to Islamic education in the digital era. The results of this research show that the integration of technology and religious values in learning promotes a deep understanding of Islamic teachings, ensuring the relevance of Islamic education amid digital transformation. This research emphasizes the need to develop traditional pedagogical methods in the era of the 5.0 Industrial Revolution. By combining interactive and innovative teaching techniques, such as e-learning platforms, multimedia presentations, and collaborative projects, educators can effectively engage students and enhance their understanding of Islamic values. Additionally, collaboration with local religious institutions and scholars enables a deeper understanding of religious practices and encourages students to apply these teachings in their daily lives driven by technology. The integration of technology and Islamic values in education is crucial, not only to preserve the essence of religious teachings but also to prepare students for the dynamic landscape of the digital era while holding firmly to their faith and moral principles.